THE IMPACT OF AFFECTIVE COMMITMENT AND LEADERSHIP COMMUNICATION ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR MEDIATED BY WORK INVOLVEMENT ON EMPLOYEES OF PT AMARA TUJUH PERJUANGAN - Fadhillah, Aulia EL; Sudiardhita, I Ketut; Wolor, Christian Wiradendi (UTSAHA: Journal of Entrepreneurship, 2023)
PT Amara Tujuh Perjuangan expects that there will be many external challenges in the next 5 years. Therefore, under this condition, it requires support from employees as valuable company assets to be able to contribute more to the company, and it is important to have good employee care and keep developing it. This research aims to determine and analyze the effect of affective commitment and leadership communication on OCB mediated by work involvement on employees of PT Amara Tujuh Perjuangan. This research method is quantitative, and data collection used survey methods. The sampling technique used nonprobability sampling: saturated sample in the form of a census. The sample for this research is employees of PT Amara Tujuh Perjuangan with a total sample size of 98 respondents. The data analysis method used in this research is Structural Equation Modeling (SEM) using SmartPLS 3.0 software. The results of this research indicate that (1) affective commitment has a positive and significant effect on organizational citizenship behavior; (2) leadership communication has a positive and significant effect on organizational citizenship behavior; (3) organizational citizenship behavior has a positive and significant effect on work involvement; (4) affective commitment has a positive and significant effect on employee engagement; (5) leadership communication has a positive and significant effect on work engagement; (6) affective commitment has a positive and significant effect on organizational citizenship behavior; (7) leadership communication has a positive and significant effect on organizational citizenship behavior. The conclusion of this research is that all hypotheses are accepted.